Penggunaan Laras Pada Kacapi Kawih Dalam Lagu Pop Sunda - Aldi Nurhadiat Iskandar (Journal on Education, 2023)
This study describes the use of the barrel on the Kacapi Kawih in Sundanese pop songs. The research method used is descriptive analysis with a qualitative approach. Along with the creativity in creating Sundanese pop songs that are packaged with uniqueness and using non-primary tones in karawitan notation, artists, especially harp players, in accompaniment to songs that are adapted to new accompaniment patterns, have been renewed. The primary notes in Sundanese karawitan, especially in Kacapi, have a 1-2-3-4-5 (da-mi-na-ti-la) arrangement consisting of 20 strings. The barrel used also depends on the needs of the song to be presented, such as the gamelan, pelog, madenda, and salendro barrels. Therefore, in one waditra Kacapi usually only uses one barrel and one trance. The concept of the barrel in this Kacapi Kawih, there is a modified arrangement of notes on the Kacapi strings. These changes are found in the lowest octave of gembyang, namely the inclusion of pelog tones 3-(ni) and 5+ (leu). Thus, in songs that contain interlude notes (insertions) outside the tonality of the tunings, the song will match the notation and accompaniment pattern of the Kacapi accompaniment